2005
DOI: 10.1164/rccm.200410-1414oc
|View full text |Cite
|
Sign up to set email alerts
|

Regional Lung Deposition and Bronchodilator Response as a Function of β2-Agonist Particle Size

Abstract: Regional targeting of inhaled beta2-agonist to the proximal airways is more important than distal alveolar deposition for bronchodilation. Altering intrapulmonary deposition through aerosol particle size can appreciably enhance inhaled drug therapy and may have implications for developing future inhaled treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
399
2
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(431 citation statements)
references
References 40 publications
15
399
2
15
Order By: Relevance
“…The use of extra-fine particle pMDIs has been Review shown to demonstrate equivalent efficacy to other preparations but with a reduced equivalent dose of corticosteroid [25][26][27][28]. These newer formulations have been reported to be less dependent upon inhaler technique than other MDIs due to longer duration of aerosol emission [29] and lung deposition being affected less by inspiratory flow [30] and coordination [31].…”
Section: Pressurized Metered-dose Inhalersmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of extra-fine particle pMDIs has been Review shown to demonstrate equivalent efficacy to other preparations but with a reduced equivalent dose of corticosteroid [25][26][27][28]. These newer formulations have been reported to be less dependent upon inhaler technique than other MDIs due to longer duration of aerosol emission [29] and lung deposition being affected less by inspiratory flow [30] and coordination [31].…”
Section: Pressurized Metered-dose Inhalersmentioning
confidence: 99%
“…This knowledge is useful since it is known that b 2 receptors predominate in the small conducting airways and alveoli; however, airway smooth muscle is present in the trachea and small conducting airways [30,38]. Consequently the ideal particle size for inhaled b 2 -agonists will be in the top end of the range of 1-5 µm, as this would allow deposition of drug particles in the region of airway where both airway smooth muscle and b 2 receptors exist.…”
Section: Inhaler Technique and Training In People With Copd And Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…[13] An advantage of small-particle instead of large-particle inhaled treatment could be a higher total lung deposition in addition to better deposition in the small airways. [4,5] Yet, we are currently not able to select asthma patients with small airway dysfunction, i.e.…”
Section: Introductionmentioning
confidence: 99%